ChemInform Abstract: Organic Thermoelectric Materials: Emerging Green Energy Materials Converting Heat to Electricity Directly and Efficiently. Issue 48 (2nd December 2014) - Zhang, Qian; Sun, Yimeng; Xu, Wei; Zhu, Daoben
Abstract Review: [101 refs.